The Role of Bugis-Makassar Cultural Values in Talent Development: A Case Study of Private Companies in Makassar - Dipoatmodjo, Tenri Sayu Puspitaningsih (Malaqbi Publisher, 2025)
This ethnographic case study examines the integration of traditional Bugis-Makassar cultural values into talent development practices within five private companies in Makassar, Indonesia. Using participant observation, focus group discussions, and in-depth interviews with 47 participants comprising executives, HR practitioners, and employees, this research explores how indigenous principles of siri' (dignity), pesse' (solidarity), and pangaderreng (customary governance) are systematically embedded throughout organizational talent management processes. The findings reveal comprehensive integration of these cultural values across the complete talent development lifecycle, from recruitment through retirement planning, demonstrating that traditional wisdom can enhance contemporary organizational effectiveness while maintaining cultural authenticity. The study shows that dignity-centered recruitment practices, solidarity-based collaborative systems, and consensus-driven governance structures create inclusive workplace environments that transcend ethnic boundaries while honoring local heritage. Organizations implementing these culturally-responsive approaches demonstrated enhanced employee engagement, strengthened organizational cohesion, and sustainable competitive advantages that extend beyond conventional human resource metrics. The research contributes to organizational behavior scholarship by providing empirical evidence that indigenous knowledge systems can be successfully operationalized within modern corporate structures without compromising efficiency or competitive positioning. For practitioners, this study offers a replicable framework for developing culturally intelligent talent management strategies that bridge traditional values with contemporary business demands. The findings suggest that effective organizational leadership in diverse cultural contexts may require thoughtful adaptation of indigenous wisdom rather than abandonment of cultural heritage, providing valuable insights for organizations operating in Southeast Asia and similar multicultural environments worldwide.